2001
DOI: 10.1002/jso.1058
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative lymphoscintigraphy and sentinel lymph node biopsy in papillary thyroid cancer. A pilot study

Abstract: These results underline the necessity to use the combination of nuclear medicine imaging and lymphatic vital dye in order to enhance the identification rate of sentinel node also in thyroid cancer. It is now necessary to check the diagnostic accuracy of this procedure through a controlled trial involving a more extended lymph node dissection in the neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 6 publications
(2 reference statements)
5
59
0
3
Order By: Relevance
“…The aims of the 12 articles included in the review analysis were: (I) to evaluate the feasibility of rSLNB in four studies (15)(16)(17)(18); (II) to compare the identification of SLN with rSLNB versus SLNB performed by a dye technique in two studies (19,20); and (III) to determine the role of rSLNB for PTC lymph node staging in six studies (9,10,(21)(22)(23)(24). Only PTC patients who underwent rSLNB were included in the analysis, achieving a total of 800 patients.…”
Section: Selection Process Of the Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The aims of the 12 articles included in the review analysis were: (I) to evaluate the feasibility of rSLNB in four studies (15)(16)(17)(18); (II) to compare the identification of SLN with rSLNB versus SLNB performed by a dye technique in two studies (19,20); and (III) to determine the role of rSLNB for PTC lymph node staging in six studies (9,10,(21)(22)(23)(24). Only PTC patients who underwent rSLNB were included in the analysis, achieving a total of 800 patients.…”
Section: Selection Process Of the Articlesmentioning
confidence: 99%
“…Injection site and intraoperative identification rate of SLN An intratumoral injection of the radiotracer was used in 10 studies (9,(15)(16)(17)(18)(19)(20)(22)(23)(24) with a median IIR of 100% (63-100%); in one study it was injected in the peritumoral space with an IIR of 91.9% (21); in one study the radiotracer was injected peritumorally in the first study period and then intratumorally to improve the preoperative visualization with an IIR of 100% (10) ( Table 1). The IIRs of the included studies are shown in Table 1.…”
Section: Radioguided Sentinel Lymph Node Biopsymentioning
confidence: 99%
See 1 more Smart Citation
“…(14) Vital blue dye method is a relative convenient SLNB technique in thyroid cancer. Isosulfan blue dye (1%), (2,8, 15-17) methylene blue (1%, 2%) (9,14,(18)(19)(20)(21)(22)(23)(24) and Patent Blue V (0.5%, 1%, 2.5%) (11,(25)(26)(27)(28) were most commonly used dyes in SLNB.…”
Section: Vital Blue Dyementioning
confidence: 99%
“…In addition, removal of parathyroid glands that had been stained by the dye is well known pitfall of blue dye methods,(9) transient vocal cord paresis attributed to a prolonged search for the SN,(10) and intravascular injection of radioisotope in one patient causing early migration of the radioisotope and non-visualization of the SN. (11) Radioactive tracer used in lymphoscintigraphy did not harm patients, surgeons or pathologists; (9,11,12) however, SLNB using lymphoscintigraphy/gamma-probe is costly and time consuming, increasing operation time.…”
Section: Introductionmentioning
confidence: 99%